Future Directions of Arabic Language Learning for Young Children in the Age of Artificial Intelligence - Fathma Zahara Sholeha (Kindergarten: Jurnal Pendidikan Anak Usia Dini Indonesia, 2026)
he rapid development of Artificial Intelligence (AI) has transformed educational practices across various disciplines, including language education. However, discussions regarding the integration of AI into Arabic language learning for young children remain limited compared to studies focusing on higher education and adult learners. This study aims to examine the characteristics of Arabic language learning in early childhood education, explore the opportunities and challenges associated with AI implementation, and propose future directions for AI-supported Arabic language instruction. This study employed a literature review approach by analyzing scholarly publications related to Arabic language education, early childhood learning, educational technology, and artificial intelligence published between 2020 and 2026, complemented by seminal works on language acquisition and child development. The findings indicate that effective Arabic language learning for young children should be grounded in meaningful social interaction, play-based learning, multisensory experiences, repetition, emotional engagement, and parental involvement. The review further reveals that AI offers significant opportunities through personalized learning, interactive storytelling, pronunciation support, adaptive instruction, teacher assistance, and enhanced home-school collaboration. Nevertheless, several challenges remain, including excessive screen exposure, reduced human interaction, linguistic limitations of AI systems, ethical and privacy concerns, cultural bias, and teacher readiness. Based on these findings, this study proposes the Human-Centered AI for Preschool Arabic Instruction (HAPI-A) Model, which integrates five key dimensions: human interaction, AI assistance, play-based learning, adaptive learning, and Islamic value integration. The model emphasizes that AI should function as a supportive educational tool rather than a replacement for human interaction. This study contributes a conceptual framework that may guide future research and educational practices concerning the integration of AI into Arabic language learning in early childhood education.